Effects of different weight-loss periods on oxidative stress state in male collegiate wrestlers - Mio, N.; Hiroki, T.; Hyeon Ki, K.; Karina, A.; Mi, X.; Masayuki, K.; Shizuo, S. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Introduction: Generation of reactive oxygen species is the physiological metabolic process of normal cells that is controlled by the antioxidant activity. High concentrations of reactive oxygen species result in damage to DNA, proteins, and lipids, which can cause cell and tissue impairment. Rapid weight loss (RWL) is characterized by transitory weight loss of at least 5% of body weight in less than a week (Khodaee et al. 2015). Rapid weight reduction in wrestlers reduced blood adiponectin level and increased their active oxygen level (Yanagawa et al. 2010). The survey of the All Japan Wrestling Championship tournament players reported that in the actual situation, wrestlers had excessive weight loss in a short period of less than 7 days. Extreme rapid weight loss rapidly increases generation of active oxygen species; thus, homeostasis might not be maintained. In the present study, we investigated the effect of different weight loss periods on the oxidative stress state in young male collegiate wrestlers. Methods We studied seven student wrestlers (weight: 66.8 ± 8.0 kg) who needed to lose weight rapidly before competing in a tournament. The experiment was conducted in three periods (7 days, 3 days, and 1 day), with a target of 5% weight loss. Each wrestler`s body composition and biochemistry index were measured at three time points, namely before weight loss, at weigh-in, and 12 hours after weigh-in. Results For the serum concentrations for the biological antioxidant potential (BAP) test, 2-factor analysis of variance revealed a significant trial-time interaction (p = 0.049). No statistically significant differences in the serum concentrations of diacron-reactive oxygen metabolites were observed between trials (p = 0.254). Conclusion The present study demonstrates that as an indicator of antioxidant potential, significant interaction was observed between trials in the BAP test.